Pediatric renal abscess: clinical analysis and literature review - Sun, Jianxin; Shi, Lina; Ye, Lezhen; Xu, Yanan (Frontiers in Pediatrics, 2025)
BackgroundPediatric renal abscesses is a severe infectious disease with a long treatment period. Due to atypical symptoms, there is a risk of delayed diagnosis, missed diagnosis, and misdiagnosis. Inadequate or incomplete treatment can lead to prolonged hospital stays, even Irreversible kidney damage. This study aimed to analyze the clinical characteristics of pediatric renal abscesses, aiming for early diagnosis and timely, appropriate treatment.MethodsA retrospective analysis was conducted on clinical manifestations, laboratory tests, imaging studies, and treatment data of 12 pediatric renal abscess cases treated in the Nephrology Department of our hospital from October 2018 to March 2023.ResultsAmong the 12 cases, there were 3 males and 9 females, aged between 7 months to 12 years. All cases were from urban areas, with fever being the primary symptom (100%), accompanied in some by abdominal pain and urinary frequency/pain. Clinical symptoms were atypical, with 91% showing elevated white blood cell count(WBC), a significant rise in neutrophil percentage, C-reactive protein (CRP), and a marked increase in procalcitonin (100%). significant elevation of urinary white blood cells in 83.3% of cases. Both urine and blood cultures were negative. All 12 cases underwent abdominal CT or Magnetic Resonance Urography (MRU), showing abscesses, all less than 3 cm. Treatment included third-generation cephalosporins, with the addition of linezolid in cases where the initial treatment was ineffective. Hospital stays ranged from 10 to 21 days. Follow-up MRU showed the disappearance of abscesses.ConclusionClinical symptoms of pediatric renal abscesses are atypical. Children with fever, accompanied by abdominal pain, and significant elevation in white blood cells, CRP, and PCT should be considered for renal abscess, and abdominal CT or MRU is recommended for early diagnosis. Conservative anti-infection treatment can yield good results for abscesses smaller than 3 cm.